Analysis of Poverty among Scheduled Castes (SCs) of District Ghazipur, U.P. : A Multidimensional Perspective - Mridul, Ajay Raj; Mishra, Anand Prasad (National Geographical Journal of India, 2022)
Poverty is one of the most complex and multi- dimensional social phenomenon that affects the all sphere of human life. The Prevailing discrimination, segregation and exploitation have evolved the nature and extent of poverty. The social formation as phenomenon on space has great significance in geographical studies which became challenging task for poverty analysis in unequal societies. The multi layers in social hierarchy are mainly represented by caste system which has many faces in its social structure. Poverty in these social organizations have varying nature in its magnitude and extent. In this context the prevalence of poverty in scheduled castes (SCs) has vital importance for understanding the mechanism of poverty in Indian society. The present paper is an attempt by authors to incorporate the various dimensions of Scheduled castes (SCs) poverty those are responsible for the overall deprivation of this particular social group. The paper also tries to establish theoretical debate based on ground reality about the Scheduled Castes (SCs) poverty on the base of different historical roots.